Recent advances in understanding the mechanisms of plant cadmium accumulation as affected by grafting in vegetable production - Zhang, Ruimin; Zhu, Youzhou; Li, Hong; Sun, Na (Frontiers in Plant Science, 2025)
Heavy metals in agricultural soils pose a major threat to food safety and human health. Among all heavy metals, cadmium (Cd) is the most problematic with contamination rates of 7% in arable land and 5.3% in facility vegetable growing soils in China. In order to employ a “remediation while producing” mode in the contaminated soils, many remediation approaches have been investigated with unsatisfactory results. Recently, grafting has been reported to have the potential of being environmentally friendly, efficient, widely applicable and low-cost for soil remediation in vegetable production. A review of recent advances in the mechanisms of Cd accumulation in plants as influenced by grafting was conducted, including the processes of root uptake and translocation to the aboveground tissues, and xylem/phloem loading. The impact of grafting on numerous aspects associated with Cd accumulation in plants was found to extend from the rhizosphere soil microbial community, rootstock genetic variation, rootstock-scion interaction to plant responses. By understanding the mechanisms of grafting in Cd detoxification, it provided a theoretical basis for the selection of rootstocks with low Cd accumulation potential and its application as an effective phytoremediation method in Cd contaminated soils.